High-grade intraventricular astroblastoma in a young adult: A rare and controversial tumor to manage - Singh, Karuna; Garg, Shipra; Rani, Shilp; Sandhu, Parvinder (Asian Journal of Neurosurgery, 2021)
Astroblastoma is a rare primary central nervous system tumor of controversial site of origin. They account for 0.45-2.8% of all primary neuroepithelial central nervous system. It has been reported in paediatric age group with bimodal age distribution affecting more females with male to female ratio being 1:11. Astroblastomas are controversial and challenging tumors in terms of diagnosis and therapeutics. Since it carries an unpredictable disease course it needs a regular follow up even for low grade tumor. Authors have tried various schedules of post op radiotherapy after maximum safe resection. Various chemotherapeutic drugs combination have also been tried without much success. We here report a 35 years old female patient who was diagnosed with high grade astroblastoma referred for post-operative radiotherapy after gross total resection. Since it is extremely rare tumor, its treatment still not well defined and also makes it difficult conduct studies to examine tumor characteristics.
Keywords: Adjuvant radiotherapy; astroblastoma; brain tumor; intraventricular tumor